A hybrid of the selected mapping and partial transmit sequence approaches for reducing the high peak average to power ratio based on multi-carrier systems – review - Ali Nahar; Mohammed A. Hussein (Computer Science and Information Technologies, 2022)
The orthogonal frequency division multiplexing (OFDM)-4G and 5G filter technology suffer a drawback that represents the direction of the peak average to power ratio (PAPR) in orthogonal frequency division multiplexing due to the nonlinear nature of the transmitter. There are a lot of traditional and hybrid methods of these traditional methods to reduce the harmful high PAPR value. Newly, several new hybrid methods have been adopted to reduce PAPR but it faces an increasing level of computational complexity in the system. In this paper, two important and effective conventional methods for reducing PAPR are studied, analyzed, and investigated for the hybrid pathway which is the incorporation of selective mapping (SLM) method and partial transport sequencing (PTS) method, which achieve increased efficiency of PAPR reduction while computing the computational complexity of each method. The method depends and balances with computational complexity. The search is based on multi-carrier connections such as multi carrier-code division multiple access (MC-CDMA) and OFDM.